New conceptions of vocational and technical education - Rosenberg, Jerry M.; Columbia Univ., New York, NY. Teachers College ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
The national conference on the need for a renewed conception of vocational and technical education, held in May 1965, assembled specialists from industry, government, and education to examine the major issues and concerns of vocational and technical education. Major emphasis was placed on the rapid changes in vocational education and present conditions that require a refocusing of energies in the development of new curriculums and philosophies of instruction. The dialogue of the conference concentrated on the implications of old and new vocational programs in the secondary schools, community and junior colleges, and universities. The papers presented in this document attempted to identify the major issues in vocational and technical education and the demands made on educational institutions to recognize the needs in the present and future world of work. Papers presented were (1) "what is vocational and technical education," by carl J. Schaefer, (2) "key issues and problems in vocational and technical education," by eli ginzberg and dale hiestand, (3) "the vocational education of the semiskilled," by donald super, (4) "work and vocational education," by charles de carlo, (5) "labor force trends and the course of vocational education," by seymour wolfbein, and (6) "vocational education for a changing world," by paul rosenbloom. This document is available for $1.25 from teachers college press, Columbia university, 525 west 120th street, New York, New York 10027. (wb)
Contract Number: OEC-5-85-089.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conferences; Educational Problems; Employment Patterns; Program Development; Semiskilled Occupations; Technical Education; Technological Advancement; Unemployment; Vocational Education; Youth Employment